3又 2分之1-(-2又4分之1)+(-3分之1)-0.25+(+6分之1)
4个回答
3又 2分之1-(-2又4分之1)+(-3分之1)-0.25+(+6分之1)
=(3+2)+(1/2+1/4-1/3-0.25+1/6)
=5+1/3
=16/3
相关问题
-1又2分之1+1又3分之1+(-5/6)=?②3又2分之1+|-2又4分之1|+(-1/3)-0.25+|+1/6|=
1、3又4分之3-(2又6分之1-0.25)
(0.3+(二又3分之2-1.25)/2又6分之5)*1又4分之3
(-3又7分之1)÷(4又6分之1-12又2分之1 )÷(-25分之11)×(-1又4分之3)
6又5分之2-(0.15+4又3分之2)=,1又3分之1-0.5+2又12分之1=
-35又3分之1-【5又4分之1+(-3又7分之1)-5.25-2又7分之6】
第一题:-2又3分之4-(-3又6分之1+0.25)第二题:-1又4分之1*(-2)+1.25*(-15)-(-125%
31又2分之1*3分之2+41又3分之1*4分之3+51又4分之1*5分之4+61又5分之1*6分之5+71又6分之1*
计算:(-2又5分之3)+(+3又4分之1)+(-3又5分之2)+(+2又4分之3)+(-1又2分之1)+【+1又3分之
计算:(-35又4分之3)*(1又7分之4)+10又2分之1*(-13又7分之6)+(-25又4分之1)*(-1又7分之